Evaluation of the relationship between testosterone levels and burnout levels and job satisfaction in emergency department female employees; a prospective study - Atik, Dilek; Basar Cander; Bensu Bulut; Hilmi Kaya; Ramiz Yazici; Ramazan Guven; Cemal Kazezoglu (Journal of the Pakistan Medical Association, 2020)
Objective: To evaluate the effect of testosterone on the status of burnout and job satisfaction. Methods: The prospective study was conducted at the Kanuni Sultan Suleyman Education and Research Hospital, Istanbul, Turkey, from April 1 to May 1, 2019, and comprised all female employees working in the emergency department. Data was collected using the Maslach Burnout Inventory and Minnesota Job Satisfaction Scale. Blood samples 5 cc were taken to measure the testosterone hormone level. Data was analysed using SPSS 20. Results: There were 95 females with a mean age of 33.6±7.1 years (range: 18-53 years). The level of exhaustion was high in 64(67.3%) subjects, intermediate in 20(21%) and low in 11(11.5%). the difference among the groups in relation to testosterone levels was significant (p<0.05). Though the difference in testosterone levels in the groups in terms of job satisfaction was also noted, it was not statistically significant (p>0.05). Conclusion: Hormone levels released from endocrine systems were found to be affected by psychosocial factors. Key Words: Testosterone, Burnout Syndrome, Job satisfaction. Continuous...